Evaluation of Sustainable Performance of Industry 4.0 Technologies Using a Novel Fuzzy OPLO-POCOD Method - Reza Sheikh; Soheila Senfi (Applied Computational Intelligence and Soft Computing)
In the rapidly evolving landscape of decision-making, particularly amid the complexities of managing extensive data, it is crucial to develop methodologies that facilitate informed choices. This paper presents a novel technique designed to address multicriteria decision-making (MCDM) challenges through the opportunity losses-based polar coordinate distance (OPLO-POCOD) method. By integrating the principle of opportunity losses—a fundamental concept in economics and management—into the evaluation process, this approach enhances the decision-making framework, providing a clearer understanding of the trade-offs involved in selecting alternatives. The innovative methodology is applied to assess the sustainability impact of Industry 4.0 technologies within Iran’s automotive industry, a sector facing unique challenges such as the need for technological adaptation. Utilizing the fuzzy OPLO-POCOD method, the study analyzes various sustainable performance indicators, ultimately identifying simulation, blockchain, and radio frequency identification as critical enablers of sustainable development. These technologies exhibit remarkably low opportunity loss scores of 0.0212, 0.0232, and 0.0270, respectively, underscoring their pivotal roles in enhancing energy and resource efficiency in production activities. This research provides significant insights for industry stakeholders and policymakers, emphasizing the importance of integrating advanced technological solutions into sustainable development strategies. By aligning technological advancements with sustainability objectives, this study not only illuminates the transformative potential of Industry 4.0 technologies but also paves the way for future inquiries in this essential field, offering a strategic roadmap for promoting sustainable practices in the automotive sector and beyond.